2012
DOI: 10.5902/198050985092
|View full text |Cite
|
Sign up to set email alerts
|

Estabelecimento e desenvolvimento <i>in vitro</i> de <i>Eugenia involucrata</i> DC.: influência do tipo de explante e do meio nutritivo

Abstract: Apresentando diversas características de interesse nos setores da silvicultura, fruticultura, meio ambiente e medicinal, Eugenia involucrata DC. (Myrtaceae) é uma espécie florestal nativa de vários Estados brasileiros. Considerada a dificuldade da propagação por sementes, que são recalcitrantes, perdendo rapidamente sua viabilidade após a colheita, este trabalho objetivou avaliar a influência do uso de segmentos apicais e nodais cultivados em diferentes meios nutritivos no estabelecimento e no desenvolvimento … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 2 publications
0
10
0
13
Order By: Relevance
“…Phenol oxidation, which is associated with the dark coloring of the explant, is another impediment to be overcome during the establishment of ligneous plants in vitro. According to Golle et al (2012), the presence of oxidation in the explants, though undesirable, do not appear to hinder the establishment and development of the cultures in vitro. This was not confirmed in the present study because the oxidation compromised E. pyriformis micropropagation in a way that did not allow us to evaluate the development of the plants in vitro.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenol oxidation, which is associated with the dark coloring of the explant, is another impediment to be overcome during the establishment of ligneous plants in vitro. According to Golle et al (2012), the presence of oxidation in the explants, though undesirable, do not appear to hinder the establishment and development of the cultures in vitro. This was not confirmed in the present study because the oxidation compromised E. pyriformis micropropagation in a way that did not allow us to evaluate the development of the plants in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…Phenols and other exudates in in vitro cultivation systems can compromise the micropropagation process, since they inhibit the initial growth of the explants, which may lead to its death (BASSAN et al, 2006). The concentration of such compounds is related to the type of explant used, with nodal segments usually presenting lower concentrations than do apical segments (GOLLE et al, 2012), which justifies the addition of antioxidant substances to the culture media.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that different MS salt concentrations influence growth in several species (Assis et al 2012;Martins et al 2015;Shekhawat et al 2015;Singh et al 2015). Generally, lower salt concentrations stimulate rooting (Sorace et al 2008;Golle et al 2012;Shekhawat et al 2015). Fargoso Monfort et al (2018) found that in Ocimum basilicum volatile constituents diminished with higher salt concentrations.…”
Section: Improvements In Traditional Culturing Techniquesmentioning
confidence: 99%
“…Esta fruteira é considerada por muitos autores, como de difícil propagação, uma vez que ao usar as técnicas assexuadas de estaquia (LOUROSA et al, 2011), alporquia (HOSSEL et al, 2014, cultivo in vitro (GOLLE et al, 2012;PAIM, 2011) DANNER et al (2011) e HOSSEL et al (2013 como eficiente em sementes deoutra recalcitrante, a jabuticabeira (Plinia sp. ).Esta técnica promove a retirada de oxigênio do ambiente das sementes, reduzindo a respiração e o metabolismo das mesmas, além de diminuir as trocas gasosas com o ambiente, aumentando-se os níveis de gás carbônico e reduzindo-se do oxigênio, o que mantém assim a viabilidade por maior período.…”
Section: Introductionunclassified